2022
DOI: 10.3390/w14040588
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Eight Cannabinoids and One Tracer in Wastewater and River Water by SPE-UPLC–ESI-MS/MS

Abstract: The consumption of illicit drugs represents a global social and economic problem. Using suitable analytical methods, monitoring, and detection of different illegal drugs residues and their metabolites in wastewater samples can help combat this problem. Our article defines a method to develop, validate, and practically applicate a rapid and robust analytical process for the evaluation of six naturally occurring cannabinoids (CBG, CBD, CBDV, CBN, THC, THCV), two cannabinoids in acidic form (CBDA, THCA-A), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In addition, Boleda et al (2009) found concentrations ranging from 11.3-127 ng/L THC and 23.5-402 ng/L THC-COOH in the influent, and 20.5 ng/L THC and 14.8-71.7 ng/L THC-COOH in the effluent of wastewater treatment plants in Catalonia, Spain.Although there is currently no data regarding CBD concentrations in wastewater, I predicted that it may closely follow that of THC because of its similar structure, availability and frequency of use. For instance,Milan et al (2016) found similar levels of THCA and CBDA (73 and 79 ng/L, respectively) in wastewater from Porto, Portugal. However, they did not find measurable amounts of THC, CBD, or THC-COOH.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, Boleda et al (2009) found concentrations ranging from 11.3-127 ng/L THC and 23.5-402 ng/L THC-COOH in the influent, and 20.5 ng/L THC and 14.8-71.7 ng/L THC-COOH in the effluent of wastewater treatment plants in Catalonia, Spain.Although there is currently no data regarding CBD concentrations in wastewater, I predicted that it may closely follow that of THC because of its similar structure, availability and frequency of use. For instance,Milan et al (2016) found similar levels of THCA and CBDA (73 and 79 ng/L, respectively) in wastewater from Porto, Portugal. However, they did not find measurable amounts of THC, CBD, or THC-COOH.…”
mentioning
confidence: 84%
“…Notably, CBD and its metabolites have not been detected in any water; however, there have been limited sampling efforts. One study also attempted and failed to find measurable amounts of CBD in wastewater from the USA (Asimakopoulos et al 2017), while another detected the acid forms of CBD and THC (CBDA and THCA, respectively) in wastewater from Portugal (Milan et al 2016). Currently, it is unknown how aqueous cannabinoids may impact most aquatic organisms at the lethal or sublethal level, especially at estimated levels of exposure.…”
Section: Cannabinoids Found In Fresh Watermentioning
confidence: 99%
“…It has been widely reported in the literature that the concentration of these two classes of substances in environmental water and sewage samples ranges from ng/L to µg/L [15][16][17]. In order to meet this detection requirement, most methods adopt offline solid phase extraction (Offline-SPE) as the pre-treatment and concentration technology of sewage [18][19][20]. The process mainly includes pre-filtration, pH adjustment, solid phase extraction, elution, concentration, and re-dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Sample pre-treatment is a crucial step implemented before chromatographic analysis to extract target analytes from the complex matrix of the sample, minimize interference from matrix components, and enhance the sensitivity of the analytical method. 16,32 Commonly used pretreatment techniques include solid-phase extraction (SPE), 16,[33][34][35] liquid-liquid extraction (LLE), 16,36 liquid-phase microextraction (LPME) 37,38 and solid-phase microextraction (SPME) 27,28,39 for WBE analysis. For example, Wang et al employed an SPE-GC-MS method for the detection of methamphetamine in wastewater in Dalian from 2015 to 2018.…”
Section: Introductionmentioning
confidence: 99%